Penile circumference in the Chinese population measured by Rigiscan - Hui Zhang; XuChong Tu; Elena Colonnello; Chunlin Wang; Emmanuele A. Jannini; Yan Zhang (The Aging Male, 2024)
Background: This study aimed to assess the penile circumference in its flaccid and erect states using a Rigiscan monitoring device and Audiovisual Sexual Stimulation (AVSS) within a large Chinese male cohort to establish an objective standard. Methods: 1,134 men participated between January 2019 and June 2021. 803 men, achieving a hardness of 80% or more, were included. Circumferences of the penis’ base and tip in its flaccid and erect states were documented, and averages were compared across age groups and Chinese regions. Age-related correlations were explored. Results: Flaccid penile base and tip averaged 7.25 ± 0.60 cm and 7.20 ± 0.71 cm. At 80% erection, they were 9.70 ± 0.65 cm and 9.65 ± 0.75 cm. The increase in circumference from flaccid to 80% erect for the base and tip was approximately 25.31% and 25.47%, respectively. Correlations between flaccid and erect states were significant (tip: R = 0.807, base: R = 0.828, both p < 0.01). No significant age or regional variations in penile circumference were found. Conclusion: Our data on 803 subjects measured with Rigiscan showed that penile circumferences in flaccid and erect states show a strong correlation, in Chinese population. Penile size does not seem significantly influenced by age or region.